2020
DOI: 10.1177/1550059420925697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation on Visual Neuroplasticity in Schizophrenia

Abstract: People with schizophrenia (SZ) exhibit visual processing abnormalities that affect their daily functioning and remediating these deficits might help to improve functioning. Transcranial direct current stimulation (tDCS) is a potential tool for perceptual enhancement for this purpose, though there are no reports of tDCS applied to visual cortex in SZ. In a within-subject, crossover design, we evaluated the effects of tDCS on visual processing in 27 SZ. All patients received anodal, cathodal, or sham stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…Contrary to our results, Gomes et al did not find a significant difference in Visual learning and working memory following 10 sessions of 2 mA tDCS on left DLPFC in patients with schizophrenia (Gomes et al, 2018). Another study found the detrimental effects of cathodal and anodal tDCS (on visual cortex) on visual processing tasks (Jahshan et al, 2020). Neither investigation used psychosocial rehabilitation and cognitive trials during stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our results, Gomes et al did not find a significant difference in Visual learning and working memory following 10 sessions of 2 mA tDCS on left DLPFC in patients with schizophrenia (Gomes et al, 2018). Another study found the detrimental effects of cathodal and anodal tDCS (on visual cortex) on visual processing tasks (Jahshan et al, 2020). Neither investigation used psychosocial rehabilitation and cognitive trials during stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…Working memory performance and auditory deviance detection were increased by anodal frontal and temporal tDCS (Impey et al, 2017). The plasticity effect following occipital tDCS was not found during anodal and cathodal stimulation (Jahshan et al, 2020). Although significant positive effects were not observed in the investigations, a comparison of the results reveals the importance of parameter selection and emphasizes comprehensive research requirements for future studies.…”
Section: Schizophreniamentioning
confidence: 87%